Influences of semantic and syntactic incongruence on readiness potential in turn-end anticipation - Wesselmeier, Hendrik; Jansen, Stefanie; Müller, Horst M. (Frontiers in Human Neuroscience, 2014)
Knowing when it is convenient to take the turn in a conversation is an important task for dialog partners. As it appears to be that this decision is made before the transition point has been reached, it seems to involve anticipation. There is a variety literature that gives possible explanations for turn-end anticipation. This study in particular focuses on how turn-end anticipation rely on syntactic and/or semantic information during utterance processing, tested with syntactically and semantically violated sentences. In a combination of a reaction time and EEG experiment, we used onset latencies of the readiness potential (RP) to uncover possible differences in response preparation. Even though the mean Anticipation Timing Accuracy (ATA) of the behavioral test were all within a similar time range (control sentences: ATA 108 ms, syntactically violated sentences: 92.6 ms, semantically violated sentences 115.6 ms), we found evidence that response preparation is indeed different for syntactically and semantically violated sentences in comparison to control sentences. Our RP results, which are based on preconscious EEG-data, showed a response preparation onset to sentence ending interval of 1522 ms in normal sentences, 707 ms in sentences with syntactic violations and 944 ms in sentences with semantic violations. Compared to control sentences, this resulted in a significant RP onset delay, for both sentences with syntactic and semantic violations and indicates a delay of preconscious response preparation.